2005
DOI: 10.1021/jf048177q
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Wine Phenolics Catechin, Quercetin, and Resveratrol Efficiently Protect Hypercholesterolemic Hamsters against Aortic Fatty Streak Accumulation

Abstract: The effects of the phenolic compounds catechin (Cat), quercetin (Qer), and resveratrol (Res) present in red wine on early atherosclerosis were studied in hamsters. Hamsters (n = 32) were divided into 4 groups of 8 and fed an atherogenic diet for 12 weeks. They received by force-feeding 7.14 mL/(kg of body wt.day) Cat, Qer, or Res in water [2.856 mg/(kg of body wt.day) for Cat and 0.1428 mg/(kg of body wt.dday) for Qer and Res], mimicking a moderate consumption of alcohol-free red wine (equivalent to that suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
72
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 62 publications
(75 reference statements)
14
72
1
1
Order By: Relevance
“…Oral administration of AAE (150 mg/kg/d bw) had a distinct cholesterol- Table 2 Table 2 lowering effect by decreasing the levels of serum TC, hepatic TC and TG, accordingly reduced the risk of CHD. Similar cholesterol-lowering results had been previously reported in many polyphenolic compounds from different plant foods (Auger et al 2005;Suzuki et al 2005). AI has direct correlation with the cardiovascular disease.…”
Section: Resultssupporting
confidence: 88%
“…Oral administration of AAE (150 mg/kg/d bw) had a distinct cholesterol- Table 2 Table 2 lowering effect by decreasing the levels of serum TC, hepatic TC and TG, accordingly reduced the risk of CHD. Similar cholesterol-lowering results had been previously reported in many polyphenolic compounds from different plant foods (Auger et al 2005;Suzuki et al 2005). AI has direct correlation with the cardiovascular disease.…”
Section: Resultssupporting
confidence: 88%
“…It is well established that RSV is associated with a reduced risk of cardiovascular diseases. Although its effect on endothelial hyperpermeability was rarely reported, RSV was shown to inhibit accumulation of fatty streak, the first grossly visible lesion in the development of atherosclerosis (Auger et al 2005). In the present study, RSV co-incubation was observed to ameliorate the high-glucose-induced hyperpermeability in aortic endothelial monolayer cells.…”
Section: Discussionsupporting
confidence: 46%
“…Prodelphinidins are only present in grape skin and their monomers are [(+)-catechin, (−)-epicatechin, (+)-gallocatechin and (−)-epigallocatechin units] ( Figure 3). Proanthocyanidins (procyanidins and prodelphinidins) are the major phenolic compounds in grape seed and skins [39], about 60-70% of total polyphenols are stored in grape seeds [40][41][42]. According to several published works [43,44], on average and on the basis of fresh weight, the concentrations of proanthocyanidins are as follows: total monomers ((+)-catechin and (−)-epicatechin), 2-12 mg/g in seeds and 0.1-0.7 mg/g in skins; total oligomers, 19-43 mg/g in seeds and 0.8-3.5 mg/g in skins and total polymers, 45-78 mg/g in seeds and 2-21 mg/g in skins.…”
Section: General Introductionmentioning
confidence: 99%